Solanaceae Leaves as are Sources of Antioxidants and Vitamin D - Ekaterina E. Borodina; Oksana V. Kozlova; Veronika Yu. Boger; Larisa A. Proskuryakova; Vladimir P. Yustratov (Техника и технология пищевых производств)
Coal miners work underground, which means they are likely to be at greater risk of developing Vitamin D deficiency due to reduced sunlight exposure. Other industrial health risks may include oxidative stress, respiratory diseases, and inflammatory pathologies. Leaves of nightshade plants are rich in antioxidants, which means they can prevent mining-related diseases, compensate for vitamin D deficiency, and counteract oxidative stress at the cellular level. The article describes the component composition of the leaves of various Solanaceae plants to be used in functional foods fortified with antioxidants and vitamin D. The research featured dried leaves of tomato (Solanum lycopersicum L.), potato (S. tuberosum L.), black nightshade (S. nigrum L.), and bittersweet nightshade (S. dulcamara L.). The antioxidant studies involved a comprehensive analysis of flavonoids, chlorophyll, carotenoids, and volatile organic compounds using ABTS and DPPH radicals. The vitamin D content was studied by high performance liquid chromatography. The leaves proved to be rich in flavonoids, chlorophyll, carotenoids, and volatile organic compounds. The high antioxidant potential was confirmed by ABTS and DPPH tests. The highest content of vitamin D belonged to potato leaves (224.7 μg/100 g) and black nightshade (22.8 μg/100 g), demonstrating good prospects for food fortification. The high antioxidant content in the leaves of tomato, potato, black nightshade, and bittersweet nightshade makes them a promising raw material for the functional food industry. They may be able to improve the health of miners and prevent industrial diseases.